2017
DOI: 10.1002/anie.201708637
|View full text |Cite
|
Sign up to set email alerts
|

Transient Behavior of the Metal Interface in Lithium Metal–Garnet Batteries

Abstract: The interface between solid electrolytes and Li metal is a primary issue for solid-state batteries. Introducing a metal interlayer to conformally coat solid electrolytes can improve the interface wettability of Li metal and reduce the interfacial resistance, but the mechanism of the metal interlayer is unknown. In this work, we used magnesium (Mg) as a model to investigate the effect of a metal coating on the interfacial resistance of a solid electrolyte and Li metal anode. The Li-Mg alloy has low overpotentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(156 citation statements)
references
References 46 publications
5
151
0
Order By: Relevance
“…Interestingly, the interfacial resistance decreases to 12 Ω cm 2 after 100 cycles at 200 µA cm −2 and 60 °C (Figure a), which is due to the improved contact between metallic Li and the SE (Figure S5b, Supporting Information). The interfacial resistance in our work is comparable to or even lower than those at the Li/oxide SE interfaces, although interfacial modifications with Al 2 O 3 (≈1 Ω cm 2 ), Al (≈75 Ω cm 2 ), Mg (≈70 Ω cm 2 ), Carbon (≈105 Ω cm 2 ), and polymer (≈220 Ω cm 2 ) were conducted in previous works.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, the interfacial resistance decreases to 12 Ω cm 2 after 100 cycles at 200 µA cm −2 and 60 °C (Figure a), which is due to the improved contact between metallic Li and the SE (Figure S5b, Supporting Information). The interfacial resistance in our work is comparable to or even lower than those at the Li/oxide SE interfaces, although interfacial modifications with Al 2 O 3 (≈1 Ω cm 2 ), Al (≈75 Ω cm 2 ), Mg (≈70 Ω cm 2 ), Carbon (≈105 Ω cm 2 ), and polymer (≈220 Ω cm 2 ) were conducted in previous works.…”
Section: Resultssupporting
confidence: 59%
“…It is difficult for an individual polymer or oxide to achieve fast lithium ion transportation both in the SE and across the electrode/SE interface. Therefore, interfacial modifications, such as Al 2 O 3 , Mg, and carbon, which can alloy with metallic Li, were used to lower the interfacial resistance between metallic Li and oxide‐based SEs. Furthermore, Goodenough and co‐workers created a polymer/ceramic/polymer sandwich‐structured electrolyte to decrease the resistances at the Li/SE and cathode/SE interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…[26,32,33] Quite a number of studies reported on lithium alloying interlayers, such as Ge, Al, Sn, Au, Si, Mg, and Ag, aiming to improve the interface kinetics. [24,39,41,42] Thus one must assume that most of the interlayers mainly act as contact mediator during cell assembly and new solutions need to be found to address and circumvent the vacancy diffusion limitation of lithium metal anodes. [41,42] A closer look shows that the operating principle of alloys and alloy interlayers is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the coating layer should be as thin as possible (nanometers) to decrease the migration distance of Li + ions. K. Fu et al [203] employed the vapor decomposition method to prepare an ultrathin Mg layer (5-100 nm) on the LLZO. Some metallic and nonmetallic elements can be employed to modify the SSEs.…”
Section: Interface Engineering To Minimize the Interfacial Resistancementioning
confidence: 99%
“…2019, 9,1901810 Reproduced with permission. [203] Copyright 2017, Wiley. e) Schematic diagram indicating that insertion of Ge film between LAGP and Li hindered the LAGP from being reduced.…”
Section: Interface Engineering To Minimize the Interfacial Resistancementioning
confidence: 99%